Chemically Synthesized, Self‐Assembling Small Interfering RNA‐Prohead RNA Molecules Trigger Dicer‐Independent Gene Silencing. Issue 8 (12th January 2022) - Hill, Alyssa C.; van Leeuwen, Daniël; Schlösser, Verena; Behera, Alok; Mateescu, Bogdan; Hall, Jonathan
Abstract: RNA interference (RNAi) mediated by small interfering RNA (siRNA) duplexes is a powerful therapeutic modality, but the translation of siRNAs from the bench into clinical application has been hampered by inefficient delivery in vivo. An innovative delivery strategy involves fusing siRNAs to a three‐way junction (3WJ) motif derived from the phi29 bacteriophage prohead RNA (pRNA). Chimeric siRNA‐3WJ molecules are presumed to enter the RNAi pathway through Dicer cleavage. Here, we fused siRNAs to the phi29 3WJ and two phylogenetically related 3WJs. We confirmed that the siRNA‐3WJs are substrates for Dicer in vitro. However, our results reveal that siRNA‐3WJs transfected into Dicer‐deficient cell lines trigger potent gene silencing. Interestingly, siRNA‐3WJs transfected into an Argonaute 2‐deficient cell line also retain some gene silencing activity. siRNA‐3WJs are most efficient when the antisense strand of the siRNA duplex is positioned 5′ of the 3WJ (5′‐siRNA‐3WJ) relative to 3′ of the 3WJ (3′‐siRNA‐3WJ). This work sheds light on the functional properties of siRNA‐3WJs and offers a design rule for maximizing their potency in the human RNAi pathway. Abstract : Chimeric molecules fusing small interfering RNA (siRNA) duplexes to prohead RNA (pRNA) three‐way junctions (3WJs) were designed. The siRNA‐3WJs self‐assembled in vitro. siRNA‐3WJs transfected into Dicer‐deficient cell lines triggered potent gene silencing. siRNA‐3WJs are most efficient when the antisense strand of the siRNA duplex is positioned 5′ of the 3WJ (5′‐siRNA‐3WJ) relative to 3′ of the 3WJ (3′‐siRNA‐3WJ).